KETIDAKTEPATAN KODE KOMBINASI HYPERTENSI PADA PENYAKIT JANTUNG DAN PENYAKIT GINJAL BERDASARKAN ICD 10 DI RUMAH SAKIT ISLAM IBNU SINA PEKANBARU - I Made Sudarma Adiputra; Ni Luh Putu Devhy; Kadek Intan Puspita Sari (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
Code is provision fixing code by using letters and numbers or combination of letters and numbers that represent data component. Based on the preliminary survey result from 10 medical record file on diagnosis of hypertension combination, heart disease and kidney disease founded 6 (six) of them are wrong code. The objective of this research is to determine of inaccuracy disease code for hypertension complication of heart disease and kidney disease at Islamic Hospital Ibnu Sina Pekanbaru. The method use in this research is mix method (quantitative & qualitative). The populations in this research are 52 of inpatient medical record file taken by total sampling. The result of this research obtained that inpatient medical record file which accurate in determining of combination code are 21 (40%) and inpatient medical record file which inaccurate in determining of combination code are 31 (60%). The factor that causes inaccuracy of hypertension code combination in heart disease and kidney disease is due to lack competence of medical recorder in coding.